Gender Fair Education As A Counter Feminization of Poverty Movement in Women's Schools in Gresik Regency - Nadlir, Nadlir; Fahmi, Muhammad; Prasetia, Senata Adi; Muallifah, Ilun (UIN Sunan Kudus, 2023)
This article explores the design and implementation of Gender Fair Education as a counter-feminization of poverty movement in women's schools in Gresik Regency. Based on data from women and gender observers, poverty studies have not paid sufficient attention to the gender dimension of poverty. It was from these data that the expression “women are the poorest of the poor” and the term “feminization of poverty” arose. This article is the result of qualitative-explorative research with a phenomenological approach and data retrieval through observations, interviews, documentation, and focus group discussion. The findings showed that gender-fair education as a counter-feminizationof the poverty movement was designed through the Gender Watch program. It is a women's empowerment program through the establishment of women's schools with gender-fair education materials as the curriculum. The implementation of gender-fair education is manifested through the establishment of women's schools in villages in Gresik Regency. The program like this is important to be replicated in other places as an effort to achieve gender equality and justice.